Sejarah Masjid Agung Manonjaya - Zainuddin Zainuddin (Jurnal Lektur Keagamaan, 2014)
Great Mosque of Manonjaya-Tasikmalaya is a historic ancient mosque, heritage from Nagara Sukapura (1632-1901 AD), in the realm of culture heritage objectswhich are protected by the Antiquities Act. This mosqueis a witnessof entrance and development of Islam in East Priangan–West Javawhich is in contact with the regents when they preach Islam tohis people. In this regard, Sheikh Abdul Muhyihad contributed in putting the base of Islam in this region. He,the clericfrom Pamijahan, was a teacher of theregents and their family. He also laid the first stone of the mosque construction from mushola (small mosque). The Change from musholato mosque was initiated by the Regent Sukapura VIII, Kangjeng Dalem Wiradadaha (1814 - 1837 AD). Manonjaya Great Mosque was rebuild in 2010 AD after the earthquake shattered this mosque in 2009 AD. Manonjaya Great Mosque now seems sturdy and graceful, located on the border of West Java and Central Java. Keywords:  Mosque, Sukapura, Sheikh Abdul Muhyi